Category Shift of Noun Phrases in the Movie “Avengers: Infinity War” - Ardliansyah, Muhammad; Tri Ediwan, I Nyoman (Humanis; Vol 23 No 4 (2019)DO - 10.24843/JH.2019.v23.i04.p01, 2019)
The translation of the film “Avengers: Infinity War” from English into Indonesian has many category shifts occurrences. This study with the title “Category Shift of Noun Phrases in the Movie “Avengers: Infinity War” has two research problems: (a) what kinds of category shifts can be found in the translation of the film “Avengers: Infinity War” from English into Indonesian, and (b) how do category shifts applied in the translation of the film “Avengers: Infinity War” from English into Indonesian. The purposes of this study are to find and describe and analyse the kinds of category shifts occurred in the translation of the film “Avengers: Infinity War” from English into Indonesian, and to describe how the category shifts occurred in the translation of the film “Avengers: Infinity War” from English into Indonesian. The data were collected from the film “Avengers: Infinity War” itself with its Indonesian subtitle. The data were in form of noun phrases, in which category shifts occurred. They were collected using observation and documentation methods. The data were then analysed using descriptive and qualitative method. This study is limited to the analysis of the category shift occurrences of noun phrases in the English-Indonesian subtitle using the theory of translation shift proposed by Catford. The result of this study is that all kinds of category shifts were found in the data, such as shift of structure, shift of class, unit shift and intra-system shift. Category shifts occurred in the English-Indonesian subtitle due to the different grammatical structure, the different word classes, the different ranks, and the different internal systems of a source language and a target language.